Pengaruh Kegiatan Reading Time Terhadap Kemampuan Literasi Informasi Siswa di Perpustakaan SMA N 1 Jetis - Ajeng Diah Mawartiningsih; Dr. Sri Rohyanti Zulaikha, S.Ag., SS., M.Si. (THE LIGHT : Journal of Librarianship and Information Science, 2021)
This study aims to determine the impact of Reading Time activities on students' information literacy skills in the library of SMA N 1 Jetis. The research method used in this research is descriptive quantitative. The sample obtained amounted to 74 respondents with the Yammane formula. The sampling technique used incidental sampling. Variable X is Reading Time activity as independent variable, Y variable is information literacy ability as dependent variable. Data collection techniques are questionnaires, interviews, observation, and documentation. The measurement scale uses a Likert scale. Data analysis used the mean and grand mean, correlation analysis and simple linear regression analysis. The results showed: (1) Reading Time Activities in the Library of SMA N 1 Jetis were included in the "Good" category from the results of the analysis of the mean and grand mean of the variable X of 3.11 in the interval 2.50 - 3.24. (2) Students' Information Literacy Ability in the "Good" category from the results of the analysis of the mean and grand mean of the Y variable of 3.23 in the interval 2.50 - 3.24. (3) The results of the hypothesis test show that H0 is rejected and Ha is accepted, which means that there is a positive influence between Reading Time activities on Students' Information Literacy Ability in the Library of SMA N 1 Jetis. The effect has a value of (0.716) which is included in the interval 0.60 - 0.799 meaning the level of the relationship is "Strong". (4) The results of the calculation of Simple Linear Regression with the equation Y= 22.447 + 1.496 X. and R Square of 0.513. It means that the influence of Reading Time activities on information literacy skills is 51%.